Maddi olmayan duran varlıkların ulusal ve uluslararası standartlara göre incelenmesi ve muhasebe kayıtları - Akgül, Tuna (My University, 2003)
TÜRKÇE Günümüz ekonomik koşulları, iktisadi işletmelerde mevcut olan maddi varlıkların yansıra maddi olmayan varlıklarında ortaya çıkmasına neden olmuştur.İşletmeler artık maddi varlıklarının yansıra maddi olmayan varlıklarınında gerçeklerini kabul etmiş bulunmakta ve bu doğrultuda gelişme çabası içindedirler. Bu nedenle günümüzde maddi olmayan varlıklar kalemi hesaplarının incelenmesi,değerlemesi ve standartlara uygun bir şekilde irdelenmeside önem kazanmıştır. Çalışmamızın konusunda bu doğrultuda tekdüzen hesap planı içinde yer alan maddi olmayan duran varlık hesaplarının ulusal ve uluslar arası muhasebe standartlarına göre incelenmesi ve muhasebe kayıtlarıdır. Muhasebenin Temel Kavramları ele alındıktan ve temel muhasebe bilgileri irdelendikten sonra ulusal ve ulusal muhasebe standartlarına değinilmiştir.Uluslararası Standartların ulusal standartlar karşısında durumu ve iki standardın karşılaştırılması bu anlamda önem kazanmaktadır. Çalışmamız daha iyi irdelemek için hem Maddi Duran Varlıklar hem de Maddi Olmayan Duran Varlıklar Uluslararası Muhasebe Standartlara göre irdelenmiş ve tanımlaması yapılmıştır. Maddi Duran Varlıkların genel anlamları ile açıklandıktan sonra araştırma konumuzun içeriği olan Maddi Olmayan Duran Varlıklara değinilmiştir.Maddi Olmayan Duran Varlıklar sırası ile niteliği,bölümlenmesi,muhasebeleştirilmesi,envanteri,ulusal standartlara göre değerlenmesi ve uluslar arası muhasebe standartlara göre değerlenmesi ele alınmıştır. INTANGIBLE ASSETS In these economic status,managements must give importance to Internetional Accounting Stardards.While the world globallising nobody can't take care of this criteria.They must take care about all the standarts while they're giving real decisions to the company.In our contry both national and international accounting standarts are used for many years.In these, the main problem is to use both national and international standards together.Internetional accounting hormanization has recently been given a boost by the decision in May 2000 by the İnternational Organization of Seceruties Commissions to endorse the İnternetional Accounting Standarts,while still allowing individual regulators to require certain supplementary treatments.Additionally,the Europen Commission proposed in Communication dated june to require all listed EU comapanies to prepare their consolited financial statements in accordence with internationa accountin standarts from 2005 onwards at the latest.This communication was followed by a proposal for regulation in Feb 2001,including the same requirement.These important decisions and propals could be expected to generate a certain optimism for players in accounting hormanization field. Our reseach's topic is about this criteria.Our reserach's topic is Intangıble Assets. First,we explained the national accountant rules and obligations that we use in our contry. We examine our topic both in national and international standards.While the world globalling the manegement's decision makers must be very carefull in this topic.First off all national acoountant rules examined next internetional accounting standards explained in this part. National standarts compared with IAS(İnternational Accounting Standards). Advanteges and disadvanteges of international accounting standards are also mentioned.National Accountant Rules are examined carefully.
Keywords: Maddi Olmayan Duran Varlıklar_Muhasebe; Muhasebe; Yönetim ve yardımcı hizmetler